Brincidofovir is a robust replication inhibitor against African swine fever virus in vivo and in vitro - Shibang Guo; Yibo Zhang; Zhankui Liu; Daozhong Wang; Hui Liu; Liang Li; Qichao Chen; Dan Yang; Qingyun Liu; Huihui Guo; Shuang Mou; Huanchun Chen; et al. (Emerging Microbes and Infections)
African swine fever virus (ASFV) infection is a major public and socioeconomic concern that has a serious impact on the global swine industry. Unfortunately, there are currently no commercially available vaccines or antiviral agents that are both safe and effective against ASFV. In the study, we use primary porcine alveolar macrophages to screen a kinase inhibitor library for anti-ASFV compounds. Six candidate compounds that inhibited ASFV infection with inhibition of > 90% were identified, among which brincidofovir exhibited optimal inhibitory effects on ASFV. Brincidofovir reduces ASFV replication in a dose-dependent manner (IC50 = 2.76 nM) without cytotoxicity (CC50 = 58 μM). It possesses the ability to reduce viral titres and inhibit viral structural protein expression. Time-of-addition assays suggest that the compound interferes with the post-invasion stage of the viral infection cycle. In pig challenge experiments, brincidofovir was indicated to protect pigs against ASFV-induced lethality by decreasing the viral load in organs and peripheral blood, while it alleviated the histopathological changes associated with ASFV infection. Furthermore, brincidofovir also decreased viral shedding in pigs with ASFV infection. Our data together demonstrate that brincidofovir may serve as a potentially effective agent for the prevention and control of ASFV infection, whereas further investigations are still required.